Comparative genetic diversity studies of Shorea curtisii (Dipterocarpaceae) an assessment using SSR and DAMD markers - Wei-Seng, Ho; Wickneswari, Ratnam; M. C., Mahani; M. N., Shukor (Forest Research Institute Malaysia, 2006)
Genetic diversity of Shorea curtisii from different age cohorts, namely, seedlings, saplings and adult trees were determined using six SSR loci and 33 DAMD loci. To quantify genetic diversity in S. curtisii we used standard genetic diversity measures for SSR data, and both phenotypic and genotypic methods with null-allele frequency corrected for deviation from Hardy-Weinberg equilibrium (HWE) with SSR markers for DAMD data. Results showed that the genetic diversity measured using DAMD genotypic method was lower than those derived from SSR data based on the same set of samples. This suggests that DAMD allele frequencies corrected from HWE deviation using fixation index derived from SSR data may be underestimated. The genetic distance matrix generated from SSR data was significantly correlated with DAMD genotype data (r = 0.990, p < 0.05), indicating a similar genetic structure of S. curtisii being depicted by both marker types among the age cohorts tested. The relationship between sample size and genetic diversity measures demonstrated a threshold level, i.e. n = 20 and n = 30 for seedlings and saplings respectively, and n = 15 and n = 20 for adult trees revealed by SSR and DAMD markers respectively. Genetic diversity measures dropped drastically below these levels. These results further imply that a highly heterogeneous population was observed in S. curtisii from each age cohort. Collectively, both SSR and DAMD markers have good genome coverage in the S. curtisii genome.